Ombitasvir/Paritaprevir/Ritonavir and Dasabuvir - Cada, Dennis J. (Hosp Pharm, 2015)
Each month, subscribers to The Formulary Monograph Service receive 5 to 6 well-documented monographs on drugs that are newly released or are in late phase 3 trials. The monographs are targeted to Pharmacy & Therapeutics Committees. Subscribers also receive monthly 1-page summary monographs on agents that are useful for agendas and pharmacy/nursing in-services. A comprehensive target drug utilization evaluation/medication use evaluation (DUE/MUE) is also provided each month. With a subscription, the monographs are sent in print and are also available on-line. Monographs can be customized to meet the needs of a facility. A drug class review is now published monthly with The Formulary Monograph Service. Through the cooperation of The Formulary, Hospital Pharmacy publishes selected reviews in this column. For more information about The Formulary Monograph Service, call The Formulary at 800-322-4349. The May 2015 monograph topics are palbociclib, lenvatinib, nivolumab, ferric pyrophosphate citrate solution, and secukinumab. The Safety MUE is on non-opioid injectable pain or fever medications.